Patient-Centeredness in Pharmaceutical Care - Al-Rusasi, Ahmad (Jordan Journal of Pharmaceutical Sciences, 2023)
Background information: Pharmacy is a longstanding profession, although there have been changes in pharmacists’ roles over time. The change toward a patient-centered approach is recognized as an entirely different concept from the technical concept of dispensing. The pharmacist’s natural attitude primarily relies on pharmacologic knowledge of medications, the product, the use of counseling as the major approach with patients, and an emphasis on medication adherence as a goal. Though, besides a pharmacologic understanding, the knowledge of the patient and the knowledge of the experience of the patient, from his or her own perspective, are essential to help the pharmacist assess and ensure that a medication is indicated, effective, safe, and convenient. Therefore, to be able to work with patients in a patient-centered manner, the pharmacist must acknowledge a broader scope of knowledge that will account for a more comprehensive approach. Conclusion: To practice in a truly patient-centered manner, pharmacist must understand that patients want to be heard and seen as individuals with unique experiences and responses to medications. This knowledge is needed to enhance pharmacists’ basic pharmacotherapeutic understanding and provide for care of patients as individuals with unique experiences and stories and situated in community, culture, and society. Likewise, to help patients with their medications, pharmacist must begin to understand medications as patients experience them. This includes understanding their experiences with illness as well as their feelings about medications.